Ever by my side [large type] : a memoir in eight [Acts] pets - Trout, Nick (Thorndike Press large print biography series., 2011)
Bestselling author Nick Trout has captivated readers with books that take us behind the scenes into the heartwarming - and sometimes heartrending - world of veterinary medicine. Now, in a perfect follow-up to his first two books, he turns his lens inward and offers a funny, moving, and thoughtful memoir about the pets he's had throughout his life and how they have shaped him into the son, father, husband, and doctor he is today.